Research on the optimal planning of the battery switch station for electric vehicles. Issue 10 (23rd September 2016) - Zhang, Yagang; Qi, Dingli; Lei, Shuang; Wu, Ke; Wang, Yinding
Abstract : With the rapid development of the global economy, the energy crisis and the deterioration of the ecosystem are becoming more serious. In this context, the development of electric vehicles has received the attention of all countries. Research on charging and changing facilities has a very important significance for the future comprehensive promotion of electric vehicles. In this study, the authors first analyse the advantages and disadvantages of different charging electric network modes. Then, they introduce distribution planning requirements of electric vehicles' changing stations, and propose an optimisation model meeting various requirements when selecting station sites. This model aims to minimise overall construction and transportation costs, and meet the charging demand of drivers. Changing stations' service types and operating characteristics of the substation act as constraint conditions. Finally, they solve the model based on the improved graph algorithms. It not only calculates the optimisation location of the changing stations, but also obtains the corresponding optimal substation access scheme. The research of this study can significantly guide planning and construction of electric vehicles' charging and battery switch stations.